Rectal misoprostol after cesarean delivery: does it affect recovery of bowel functions? A prospective randomized trial - N.K. Aref (IMR Press, 2020)
Aim: To assess the efficacy of rectally administered misoprostol in the improvement of bowel function recovery after cesarean delivery (CD). Methods: This prospective randomized trial was conducted among 171 pregnant women subjected to term elective CD. Patients were divided equally into 3 groups by simple randomization. Participants in group A were given misoprostol 200 μg rectally; those in group B were given misoprostol 400 μg rectally just after CD but before leaving the operating theater, while the participants in group C did not receive any rectal drug. The study outcome measures were: duration before first bowel movement and start of the regular oral diet. Adverse effects, need for additional analgesics, and post-CD hospital stay period were also recorded. Results: The mean times to first audible intestinal sounds and to the first passage of flatus were significantly lower in group B (14.1 ± 1.4 h and 16.7 ± 2.3 h, respectively) when compared to both groups A and C [ 21.9 ± 5.3 h and 24.9 ± 5.7 h (A) vs. 23.6 ± 6.9 h and 27.1 ± 7.9 h (C)] (p = 0.001). It was found that notably, patients in group B resumed diet more quickly, with a mean period of 20.5 h, which was significantly faster than the remaining groups (29.8 h and 33.1 h in groups A and C, respectively Of great interest, patients in group B had a lower post-CD hospital stay (38.5 h vs. 59.2 h in group A and 64. 8 h in group C). Conclusion: For the recovery of bowel functions after CD, rectal administration of 400 μg misoprostol appears to be more effective than 200 μg of rectally administrated misoprostol or traditional feeding regimens.